Challenges in diagnosis and management of coarctation of the aorta. (January 2022) - Chetan, Devin; Mertens, Luc L.
Abstract : Purpose of review: Coarctation of the aorta remains a controversial topic with uncertainties in long-term outcomes. Recent findings: Recent advances in fetal imaging including echocardiography and MRI offer novel opportunities for better detection and prediction of the need for neonatal intervention. New imaging techniques are providing novel insights about the impact of arch geometry and size on flow dynamics and pressure gradients. The importance of arch size rather than shape for optimal hemodynamics has been identified. Long-term outcome data suggest a significant increase in mortality risk in coarctation patients beyond the third decade when compared with the general population. Hypertension is highly prevalent not only in adult patients following repair of coarctation but also in normotensive patients presenting with LV diastolic dysfunction and adverse remodelling, indicating that abnormal vascular properties are important. Patients with coarctation undergoing neonatal repair are at risk for adverse neurodevelopmental outcomes and patients could benefit from timely neurocognitive evaluation and intervention. Summary: Optimizing aortic arch size, prevention and aggressive treatment of hypertension and vascular stiffening are important to improve long-term outcomes.